PANDEMI COVID-19 DALAM PERSPEKTIF DEMOGRAFI - Dwi Agus Styawan (Politeknik Statistika STIS, 2020)
Covid-19 has become a global challenge that impacts various sectors of life. Covid-19 studies from a demographic perspective are very much needed as a basis for knowing which population groups are vulnerable to being exposed to Covid-19. This study aims to examine the demographic characteristics and comorbidity of the Indonesian population who are confirmed positive for Covid-19. The data source for this research is secondary data from the Task Force for the Acceleration of Handling Covid-19 in Indonesia. This study used a descriptive method by analyzing graphs according to the demographic characteristics and comorbidity of the population confirmed positive for covid-19. The results showed that men, of productive age, and having comorbidities such as hypertension, diabetes mellitus, and heart disease are a group prone to exposure to covid-19. The male population, who are elderly, and have comorbidities have a higher risk of dying from covid-19. Therefore, the government should limit the mobility of the population, especially those of productive age and strictly implement health protocols so that the transmission of covid-19 can be stopped. In addition, the government must also provide maximum health services to the elderly population who are exposed to Covid-19 to reduce the risk of death.